(untitled) (Materiali di Estetica. Terza serie, 2020)
With Europa riconosciuta, a Mattia Verazi’s and Antonio Salieri’s «dramma per musica», was inaugurated on the 3rd August 1778 the Teatro alla Scala in Milan. The retelling of the myth of Europe, a symbol of the harmony of peoples and nations, has led to an opera that combined extraordinary spectacular effects with a dramaturgy based on strong contrasts, a rapid alternation of the scenes, short and varied musical forms. Europa riconosciuta was under the influence of Gluck’s reformed opera and followed the most recent orientations of the international musical theatre.